2006
DOI: 10.1152/ajpgi.00545.2004
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of c-Myc and Max in rat liver development

Abstract: The processes of liver development and regeneration involve regulation of a key network of transcription factors, the c-myc/max/mad network. This network regulates the expression of genes involved in hepatocyte proliferation, growth, metabolism, and differentiation. In previous studies on the expression and localization of c-Myc in the fetal and adult liver, we made the unexpected observation that c-Myc content was similar in the two. However, c-Myc was localized predominantly to the nucleolus in the adult liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…As shown in Fig. 4, the pathway analysis identified that MYC promotes FOS expression [20], and FOS in turn promotes the expression of JUN [21], which binds to TGFBR2 to adjust long-term hypoxia effects on cell proliferation and differentiation [22]. Consistent with our chip results, fos, jun, myc, and tgfbr2 were up-regulated at 2-6, 24, 24, and 72 h, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…As shown in Fig. 4, the pathway analysis identified that MYC promotes FOS expression [20], and FOS in turn promotes the expression of JUN [21], which binds to TGFBR2 to adjust long-term hypoxia effects on cell proliferation and differentiation [22]. Consistent with our chip results, fos, jun, myc, and tgfbr2 were up-regulated at 2-6, 24, 24, and 72 h, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Using the WB-F344 cells, we examined the effect of mTOR on members of the Myc signaling network using a multiplex RNase protection assay [29]. Results (Figure 2) showed that rapamycin exposure for 6 hr induced a decrease in the steady state expression of Max and Mad 4.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the expression of Cdc20 and Hells, genes involved in mitosis, are increased in WT but not in E2F2 Ϫ/Ϫ cells. Intriguingly, Myc, an immediate early gene (33), is only upregulated in E2F2 Ϫ/Ϫ mice. It is also interesting to note that WT mice show greater expression of many genes involved in key mitochondrial processes, indicative of higher mitochondrial activities.…”
Section: E2f1mentioning
confidence: 99%